Impact of complex percutaneous coronary intervention features on clinical outcomes in patients with or without chronic kidney disease. Issue 3 (24th January 2023) - Chen, Huazhen; Spirito, Alessandro; Sartori, Samantha; Nicolas, Johny; Cao, Davide; Zhang, Zhongjie; Baber, Usman; Kamaleldin, Karim; Guthrie, Jeffers; Vogel, Birgit; Sweeny, Joseph; Krishnan, Prakash; et al.
Abstract: Background: Patients with chronic kidney disease (CKD) are at higher risk of ischemic and bleeding events after percutaneous coronary intervention (PCI). Complex PCI (CPCI) is associated with higher rates of ischemic complications. Whether CPCI confers an additive risk of adverse events in CKD patients is unclear. Methods: Patients who underwent PCI at a single tertiary‐care‐center between 2012 and 2019 were stratified by CKD status and CPCI. The primary outcome was major adverse cardiac events (MACE), a composite of all‐cause death, myocardial infarction (MI), and target‐vessel revascularization (TVR) at 1‐year follow‐up. Secondary outcomes included the individual components of the primary outcome and major bleeding. Results: Out of 15, 071 patients, 4537 (30.1%) had CKD and 10, 534 (69.9%) had no CKD. Patients undergoing CPCI were 1151 (25.4%) and 2983 (28.3%) in the two cohorts, respectively. At one year, CPCI compared with no CPCI was associated with higher risk of MACE in both CKD (Adj. HR 1.72, 95% confidence interval [CI] 1.45−2.06, p  < 0.001) and no‐CKD patients (Adj. hazard ratios [HR] 2.19, 95% CI 1.91−2.51, p  < 0.001; p of interaction 0.057), determined by an excess of death, MI and TVR in CKD patients and of TVR and MI only in no‐CKD. CPCI was related with a consistent increase of major bleeding in the CKD (Adj. HR 1.49, 95% CI 1.18−1.87, p  < 0.001) and no‐CKD group (Adj. HR 1.23, 95% CI 0.98−1.54, p  = 0.071, p of interaction 0.206). Conclusion: At 1‐year follow‐up, CPCI was associated with higher risk of MACE and major bleeding irrespective of concomitant CKD. CPCI predicted mortality in CKD patients only.